Tandem utilization of CO2 photoreduction products for the carbonylation of aryl iodides - Xia, Yuan-Sheng; Tang, Meizhong; Zhang, Lei; Liu, Jiang; Jiang, Cheng; Gao, Guang-Kuo; Dong, Long-Zhang; Xie, Lan-Gui; Lan, Ya-Qian (Nature communications, 2022)
Photocatalytic CO 2 reduction reaction has been developed as an effective strategy to convert CO 2 into reusable chemicals. However, the reduction products of this reaction are often of low utilization value. Herein, we effectively connect photocatalytic CO 2 reduction and amino carbonylation reactions in series to reconvert inexpensive photoreduction product CO into value-added and easily isolated fine chemicals. In this tandem transformation system, we synthesize an efficient photocatalyst, NNU-55-Ni, which is transformed into nanosheets (NNU-55-Ni-NS) in situ to improve the photocatalytic CO 2 -to-CO activity significantly. After that, CO serving as reactant is further reconverted into organic molecules through the coupled carbonylation reactions. Especially in the carbonylation reaction of diethyltoluamide synthesis, CO conversion reaches up to 85%. Meanwhile, this tandem transformation also provides a simple and low-cost method for the 13 C isotopically labeled organic molecules. This work represents an important and feasible pathway for the subsequent separation and application of CO 2 photoreduction product. A Ni-based MOF catalyst is reported to facilitate the photocatalytic reduction of CO2 to CO, a low-value product. In tandem, the as-produced CO is used as a reactant in the Pd-catalyzed carbonylation of aryl halides and other fine organic chemicals.